The electronic nose: artificial olfaction technology - Patel, Himanshu K. (Biological and Medical Physics, Biomedical Engineering, 2014)
This book provides the basics of odor, odor analysis techniques, sensors used in odor analysis and overview of odor measurement techniques. For beginners as well researchers this book is a brief guide for odor measurement and analysis. The book includes a special chapter dedicated to practical implementation of e-nose sensor devices with software utility, which guides students to prepare projects and work in practical analysis. It also includes material from early to latest technology research available in the market of e-nose era. Students and researchers who want to learn the basics of biomedical engineering and sensor measurement technology will find this book useful.